Additions to the Genus Salacia L. (Celastraceae) of Bay Islands, India - Lakshminarasimhan, P.; Srivastava, S. K. (Indian Forester, 1993)
Salacia macrosperma Wight, S reticulata Wight and S. salacioides (Roxb.) Rolla Rao & Hemadri is reported here as additions to the genus Salacia L. of Andaman and Nicobar Islands.